Increasing the meaningful involvement of women in HIV cure-related research: a qualitative interview study in the United States - Karine Dubé; Elizabeth Barr; Morgan Philbin; Amaya Perez-Brumer; Brian Minalga; Beth Peterson; Dawn Averitt; Bridgette Picou; Krista Martel; Cecilia Chung; María Mejía; Martha Cameron; et al. (HIV Research & Clinical Practice)
Background Cisgender women represent over half of people living with HIV globally. However, current research efforts toward a cure for HIV focus predominantly on cisgender men. The under-representation of women in HIV cure clinical studies is particularly problematic given data suggesting that sex-dependent phenotypes limit scientific discovery. Objective We aimed to generate considerations to increase the meaningful involvement of women in HIV cure-related research. Materials and methods We conducted in-depth interviews with biomedical researchers and community members to better understand factors that could increase the meaningful involvement of women in HIV cure clinical trials. Participants were affiliated with academia, industry, community advisory boards, and community-based organizations, and were identified using listings from the AIDS Clinical Trials Group and the Martin Delaney Collaboratories. We used conventional content analysis to analyze the qualitative data. Results We recruited 27 participants, of whom 11 were biomedical researchers and 16 were community members. Participants included 25 cisgender women, 1 transgender woman, and 1 cisgender man. Key considerations emerged, including the need to ensure that HIV cure studies reflect HIV epidemiologic trends and having accurate representation by sex and gender in HIV cure research. To increase the meaningful involvement of women, recommendations included instituting intentional enrollment goals, frequent and mandatory reporting on enrollment, and incentives for sites to enroll women. Additional themes included the need for agency and self-determination, attention to lived experiences, trauma and healing, and adequate support for women (e.g. logistical, psychosocial, mental, emotional, and physical). Participants noted that women would be willing to participate in HIV cure trials, related procedures (e.g. biopsies), and analytical treatment interruptions. They also expressed a desired for women-centered and holistic clinical trial designs that account for intersectionality. Conclusions Our empirical inquiry extends recent calls to action to increase diversity of people involved in HIV cure research. Redressing the under-inclusion of women in HIV cure research is an urgent imperative. The entire field must mobilize and reform to achieve this goal. Meaningfully involving women across the gender spectrum in HIV cure research is needed to ensure that interventions are safe, effective, scalable, and acceptable for all people with HIV.